P‐139: Double‐side In‐plane‐switching Electrode Blue‐phase Liquid Crystal Display with Permittivity Protrusion. Issue 1 (25th September 2020) - Tian, Li-Lan; Chu, Fan; Li, Rui; Gu, Xiao-Qing; Zhou, Xiang-Xu; Wang, Qiong-Hua
Abstract : We propose a transmissive double‐side in‐plane‐switching (IPS) electrodes blue‐phase liquid crystal display (LCD) with permittivity protrusion. The potential drops very slowly in the permittivity protrusions, thus the field penetrating depth is significantly enlarged and the operating voltage is lowered. This device has the advantages of fast response time, easy manufacturing process, and low operation voltage.